Sistem Interferometer Michelson untuk Mengukur Regangan pada Mesin Uji Tarik - Budi Setyahandana; , Martanto; Ronny Dwi Agusulistyo; Agung Bambang Setyo Utomo (Jurnal Teknik Mesin (Sinta 3), 2013)
Hasdone research Michelson interferometer system along with data acquisition, which is used for measuring strain in the tensile testing machine. Moveable mirror Michelson interferometer system mounted on the specimen clamp tensile testing machine. When the load is given in the test specimen, the specimen having the length and cause of any difference wave length of the laser beam. The wave length differences cause interference, and produce an interference pattern in the form of dark-light pattern (fringe). Interference pattern will be detected phototransistor sensor signal wave form, then recorded and processed by electronic circuits and interface microcontroller circuit, as well as converted and displayed as a displacement/increase in length (strain) of the test specimen. The experimental results obtained by the Michelson interferometer system that measures the movement (displacement) of the best maximum 9 mm. Displacement measurements using aluminium specimens produced a mean standard deviation of 0.023 (0.2%) and 0.074 (0.08%), and use of low carbon steel specimen rods produce a mean deviation of 0.08 (0.72%). appears that the system is very close to the measurement interferometer with ekstensometer. Measurement accuracy at the time of the test specimen is attached to be reduced compared to the measurements on the crosshead without load, due to a growing vibration machine.